Frequency of Depression in Primary Care-Givers of Patients with Substance Use Disorders - Ahmed, Waqas; Abid Ul Abrar; Habib Ullah; Sohail, Amir; Adnan, Mian Sohail (Indus Journal of Bioscience Research, 2025)
Objectives: To determine the frequency of depression in caregivers of patients with substance use disorders. Study Design: Cross sectional (descriptive) study. Place and Duration of the study: The study was carried out in the Department of Psychiatry of Ayub Teaching Hospital, Abbottabad from 1st June to November 2024. Methodology: The study population was included, all caregivers of patients diagnosed with substance use disorders with age between 18 to 70 years of either gender and Depression was graded as per operational definition. Results: The descriptive statistics for age among the patients show that there were 83 patients, with an age range from 18 to 70 years. The mean age was 48.64 years, with a standard deviation of 17.223 years. Out of the 83 patients, 44.6% (37 patients) were male, and 55.4% (46 patients) were female. In terms of overall depression diagnosis, 27.7% (23 patients) were classified as normal, while 72.3% (60 patients) were identified as having depression. Conclusion: In conclusion, this study highlights a substantial prevalence of depression among caregivers of patients with substance use disorders, with 72.3% of patients exhibiting symptoms of depression.